2020
DOI: 10.3855/jidc.12814
|View full text |Cite
|
Sign up to set email alerts
|

Short epidemiological overview of the current situation on COVID-19 pandemic in Southeast European (SEE) countries

Abstract: We are living in times where a viral disease has brought normal life in much of the world to a halt. The novel coronavirus known as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causing coronavirus disease 2019 (COVID-19) started in December 2019 in Wuhan, China initially and in a short time crossed the European borders. After mitigating the epidemic in China, Italy became one of the most COVID-19 affected countries worldwide. International travelers are important sources of infectious diseases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 30 publications
1
41
0
4
Order By: Relevance
“…Z is the normal standard deviate corresponding to a significance level. For a significance level/precision of 5%, Z = 1.96, P is the estimated proportion from a previous study set at 61% [27]. This gave a minimum sample size of 365.…”
Section: Sample Sizementioning
confidence: 99%
See 1 more Smart Citation
“…Z is the normal standard deviate corresponding to a significance level. For a significance level/precision of 5%, Z = 1.96, P is the estimated proportion from a previous study set at 61% [27]. This gave a minimum sample size of 365.…”
Section: Sample Sizementioning
confidence: 99%
“…Bhagavathula et al [22] in a survey among HCWs reported poor knowledge of Coronavirus disease among health care workers globally. Healthcare workers are central in the fight against COVID 19 infection as they offer treatment, which makes them vulnerable to the disease [27]. Their knowledge, attitude, and practice of the preventive measures may play important role in limiting the infection among health workers and reducing the spread to patients, family, and the community.…”
Section: Introductionmentioning
confidence: 99%
“…Within three months, the infection has spread 114 countries, and resulted in more than 4000 deaths. By this time, the World Health Organization (WHO) had announced a pandemic [1]. As of August 2020, the latest data points to 21 million global COVID-19 cases, with more than 760,000 deaths since the start of the outbreak [2].…”
Section: Introductionmentioning
confidence: 99%
“…There are no studies, to our knowledge, that have investigated the current state of hand hygiene, which is key for HAIs management, in Cambodia. Moreover, considering the recent situation caused by Corona virus disease-19 pandemic, provision of health care is one important problem [15], and it is important to understand the current status of hand hygiene in Cambodia.…”
Section: Introductionmentioning
confidence: 99%